Using canavanine resistance to measure mutation rates in Schizosaccharomyces pombe. - Chen-Chun Pai; Ellen Heitzer; Sibyl Bertrand; Sophia Toumazou; Timothy C Humphrey; Stephen E Kearsey (PLoS ONE)
We constructed a panel of S. pombe strains expressing DNA polymerase ε variants associated with cancer, specifically POLES297F, POLEV411L, POLEL424V, POLES459F, and used these to compare mutation rates determined by canavanine resistance with other selective methods. Canavanine-resistance mutation rates are broadly similar to those seen with reversion of the ade-485 mutation to adenine prototrophy, but lower than 5-fluoroorotic acid (FOA)-resistance rates (inactivation of ura4+ or ura5+ genes). Inactivation of several genes has been associated with canavanine resistance in S. pombe but surprisingly whole genome sequencing showed that 8/8 spontaneous canavanine-resistant mutants have an R175C mutation in the any1/arn1 gene. This gene encodes an α-arrestin-like protein involved in mediating Pub1 ubiquitylation of target proteins, and the phenotypic resistance to canavanine by this single mutation is similar to that shown by the original "can1-1" strain, which also has the any1R175C mutation. Some of the spontaneous mutants have additional mutations in arginine transporters, suggesting that this may marginally increase resistance to canavanine. The any1R175C strain showed internalisation of the Cat1 arginine transporter as previously reported, explaining the canavanine-resistance phenotype.